Mobile-assisted language learning: A selected annotated bibliography of implementation studies 1994-2012 - Burston, Jack (My University, 2013)
Over the past 20 years, project implementation descriptions have accounted for the majority of Mobile-Assisted Language Learning (MALL) publications, some 345 in total. Those interested in MALL applications thus need to read widely to acquire an adequate perspective of MALL implementations. The intent of this bibliography is to facilitate this task by providing a comprehensive historical background of MALL applications from the first published work in 1994 to the end of 2012. To enhance the information contained in these references, over 90% of the entries are complemented by a brief (~80 word) summary. To the extent that the publication provides such information, each annotation identifies the country of origin of the study, native language (L1) and/or the second or foreign language (L2) involved, the mobile technology used, the learning area(s) targeted, the type of learners, their numbers, the duration of the study, and a summary of the results (i.e., learning outcomes and survey opinions). Since nearly 60% of MALL implementation studies appear outside of professional journals, in conference proceedings, project reports, academic dissertations, and so forth, locating copies of these publications poses a major challenge in itself. For this reason, where possible, links are included to copies of the works cited.
Keywords: Language learning; MALL; Mobile learning; Project implementation; Ubiquitous technology